ANALISIS YURIDIS TINDAK PIDANA CYBERCRIME DALAM PERBUATAN PIDANA PENCEMARAN NAMA BAIK DITINJAU DARI UNDANG-UNDANG NO. 8 TAHUN 2011 TENTANG INFORMASI TRANSAKSI DAN ELEKTRONIK DAN HUKUM PIDANA - Abdurrahman Harit’s Ketaren; Syafruddin Kalo; Marlina Marlina; Jelly Leviza (USU LAW JOURNAL, 2018)
Abstract This internet development is indeed extraordinary. The rapid development of Internet technology has also spawned new crimes in the field, such as the crime of data manipulation, espionage, sabotage, provocation, deprivation, hacking, software theft and hardware damage, defamation, cyberbullying and various other things. Then the title of this research is "Legal Analysis of Cybercrime Crimes in Defamation in the Name of the Law Number". 8 of 2011 on Transactional and Electronic Information and Criminal Law "   The applied research method is a normative legal research method. Data sources can be derived from primary legal material, legal material and tertiary legal material. Data collection techniques are literature studies (library research). The analytical method is a method of qualitative analysis On the basis of my investigations, it is known that the elements of criminal libel are contained in the Criminal Code, namely Articles 310 and 27 (3) of Law No 8 of 2011 on Information and Electronic Transactions, the elements of which are contained in the Criminal Code Items. Rules on defamation offenses can be found in KUHP Article 310 or in the laws outside the KUHP, namely 11 of 2008 on Information and Electronic Transactions (UU ITE) Article 27 (3) before the Law on Transaction and Electronic Information No In 2011, a legal vacuum came up, in which the criminal slander was only regulated by the Criminal Code because of this vacancy, and the Electronic Transaction Information Act was formed to provide legal certainty in defamation in electronic media. Decision Analysis No. 384 / Pid.Sus / 2015 / PN. Mtr, the decision did not agree with the results of this study.   Keywords: slander, cyber crime